Smagul Saduakasuly’s short stories: integration of imagery and historical principles - Kamzabekuly, Д. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The short stories «Orten», «Salmakbai, Makhambet», «Aptonomia» by Smagul Saduakasuly (Sadvokasov), famous in the fiction of the 20s of the twentieth century with the stories «Salmakbai – Sagyndyk», «Kulpash», «Kumis konyrau», the novel «Sarsenbek», differ in both imagery and historical nature. The author of these works relating to the period of Alash literature is not just a writer, but a young, but already intellectually mature political figure who took up the pen not so much by inspiration as pursuing enlightening goals. For example, for this reason Alash leader Alikhan Bukeikhan became a competent publicist and a constructive literary critic in his political career. This quality was also characteristic of Smagul Saduakasuly. The dream of youth, the views of the intelligentsia on popular and revolutionary problems in a critical historical period, the protection of the natural interests of the people under Bolshevism, socio-political, socio-economic changes - these are the primary aim of the writer. Colonialism is a deep-rooted cruel phenomenon that has existed through injustice, meanness and violence. This perfidy, which brought tragedy to many peoples of the world (in the lexicon of Alash “juan judyryq” - thick fist), kept the Kazakh people to ineffable torment and set back the development of equality and freedom. Smagul, whose mind and heart aspired to justice from a young age, understood both societies deprived of freedom, deeply delving into their negative and some positive sides. As a representative of Kazakh literature of the first quarter of the twentieth century, proceeding from the traditions of World and Russian literature, folklore, Smagul Saduakasuly relied on imagery and historical principles and on the ways of interaction of these two creative principles mastered the skill of writing. The article examines and analyzes the research and achievements of S. Saduakas-uly in the genre of short stories that have remained outside the history of literature.